Multivariate analysis of productivity and financial performance of industrial enterprises in Cartagena, Colombia - Gómez, José Morelos; Arrieta, Fabián Gazabón; Fernández, Roberto Enrique Gómez (Universidad Pedagógica y Tecnológica de Colombia, 2013)
This research paper presents the results of the evaluation of the indicators of productivity of companies certified in ISO: 9001 and their impact on the financial profit of the companies of Mamonal Industrial Zone in Cartagena. We measured the productivity reasons in order to analyze the impact of these on financial profits of this sector. In the methodological process, in the first instance, we calculated the productivity and financial indicators of the 25 companies certified in quality. Subsequently, we used the technique of multivariate data analysis, to explain the relevance and discrimination between groups of indicators of productivity and financial performance, resulting in the correlation between certified companies and increased productivity indices for 2006 to 2010, and their incidence in the financial profit, gross margin (GM) and operating margin (OM).